Pemanfaatan Biji Cempedak (Artocarpus Champeden) dalam Produksi Tempe Inovatif : Program Edukasi Mahasiswa Berbasis Kearifan Lokal - Nanik Lestariningsih; Fatimah Fatimah (Asosiasi Riset Pendidikan Agama dan Filsafat Indonesia, 2024)
Tempe is an inherent food source for Indonesians, with a large number of tempe consumers in the local community. This community service program aims to improve students' understanding and skills in processing cempedak seeds into tempe, including drying methods that allow long-term storage. This activity was carried out from July to November 2024. This activity was carried out in several stages, namely the preparation stage, the implementation stage, and the completion stage. The program on the utilization of cempedak seeds in tempeh production shows promising potential as a food innovation based on local resources. The success rate of this program is not only measured from the production aspect, but also from the transfer of knowledge to students who act as agents of change in alternative food development. Some of the advantages of this activity program are that it provides an alternative utilization of cempedak seed waste into products with nutritional value. In addition, the production cost is relatively affordable compared to the use of soybean. The disadvantage of this program is that the availability of raw materials depends on the cempedak harvest season.